Perbaikan Kualitas Semen Ayam Kampung Melalui Peningkatan Energi Metabolisme Pakan - Nining Haryuni; Lestariningsih Lestariningsih; Binti Khopsoh (Journal of Science Nusantara, 2022)
This study was intended to obtain feed with the best energy level to improve the quality of native chicken semen. This study is a biological study with 4 levels of metabolic energy (2700; 2750; 2800 and 2850 kcal/kg) using a completely randomized design (CRD) where each treatment was repeated 5 times. Each treatment used 1 native male chicken that was 80 weeks old and in good health. Increasing energy level in feed significantly (p<0.05) increased semen volume; very significant (p<0.01) improved color and increased semen consistency; but not significant (p>0.05) the effect on semen pH. The average volume of semen obtained ranged from 0.45-1.30ml; semen color score 2.25-3.00; semen consistency score 2.25-3.00 and semen pH 7.83-8.50. Increasing the energy level in the feed can improve the quality of native chicken semen. The best feed to improve the quality of native chicken semen is feed with a metabolic energy of 2850 kcal/kg.